The Structural design of ESG-Baguia school building using the cross method for portal and forced method for truss - Caetano Jose (Faculty of Engineering, Malikussaleh University, 2024)
Structural analysis is an important part that must be considered when constructing a building, therefore in this paper to design structural elements the following method is used: The plate load distribution for the beam uses the envelope method, and the earthquake load calculation uses the equivalent static method. Structural analysis calculations use the cross method for portal and force method for trusses Reinforcement design for beams uses the ACI flowchart and reinforcement design for columns uses column interaction diagram charts. With the methods and methods mentioned by the author, the following results will be obtained: Beam cross-section 0.3m x 0.5m Column cross section 0.3m x 0.4m Reinforcing bars for beams are 6D16 Reinforcing bars for columns are 6D16